The new horse-powered farm : tools and systems for the small-scale, sustainable market grower - Leslie, Stephen, 1961- (Chelsea Green Pub., 2013)
The New Horse-Powered Farm is the first book of its kind, offering wisdom and techniques for using horse power on the small farm or homestead. It sets the stage for incorporating draft power on the farm by presenting necessary information for experienced and novice teamsters alike, including getting started with workhorses; the merits of different draft breeds; various training systems for the horse and teamster; haying with horses, seeding crops, and raising small grains; in-depth coverage of tools and systems; and managing a woodlot, farm economics, education, agritourism, and more. It's a must-have resource for any farmer, homesteader, or teamster seeking to work with draft power in a closed-loop farming system.